Chemical systems, chemical contiguity and the emergence of life - Kee, Terrence P.; Monnard, Pierre-Alain (Beilstein Journal of Organic Chemistry, 2017)
Charting the emergence of living cells from inanimate matter remains an intensely challenging scientific problem. The complexity of the biochemical machinery of cells with its exquisite intricacies hints at cells being the product of a long evolutionary process. Research on the emergence of life has long been focusing on specific, well-defined problems related to one aspect of cellular make-up, such as the formation of membranes or the build-up of information/catalytic apparatus. This approach is being gradually replaced by a more “systemic” approach that privileges processes inherent to complex chemical systems over specific isolated functional apparatuses. We will summarize the recent advances in system chemistry and show that chemical systems in the geochemical context imply a form of chemical contiguity in the syntheses of the various molecules that precede modern biomolecules.
Keywords: chemical contiguity; chemical systems; geochemical environment; prebiotic synthesis; protocell